ASM Handbook : Alloy Phase Diagrams, Volume 3 - Okamoto, Hiroaki (ASM International, 2016)
Offering a better understanding of phase diagram construction and alloy system interactions, this comprehensive volume provides an invaluable resource that will aid in the reader¿s future research and engineering pursuits. --